2019
DOI: 10.1038/s41598-019-44676-4
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Oxysterols Such as Lanosterol to Restore Lens Clarity from Cataracts

Abstract: The paradigm that cataracts are irreversible and that vision from cataracts can only be restored through surgery has recently been challenged by reports that oxysterols such as lanosterol and 25-hydroxycholesterol can restore vision by binding to αB-crystallin chaperone protein to dissolve or disaggregate lenticular opacities. To confirm this premise, in vitro rat lens studies along with human lens protein solubilization studies were conducted. Cataracts were induced in viable rat lenses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 68 publications
0
33
2
Order By: Relevance
“…In contrast to the results of Zhao et al [3], Daszynski et al failed to find evidence that lanosterol has either anti-cataractogenic activity or binds aggregated lens proteins to dissolve cataracts [4]. Taken together, it was suggested that the difference in the severity and part (cortex and nucleus) of the lens opacification may explain the contradiction in the previous reports for therapeutic effect by lanosterol [3][4][5], and our study may reflect both of these studies' results. Further studies are needed to elucidate the relationships between the effects of repair and structural collapse by lanosterol and to evaluate whether the application of lanosterol can return opaque lenses to transparency.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the results of Zhao et al [3], Daszynski et al failed to find evidence that lanosterol has either anti-cataractogenic activity or binds aggregated lens proteins to dissolve cataracts [4]. Taken together, it was suggested that the difference in the severity and part (cortex and nucleus) of the lens opacification may explain the contradiction in the previous reports for therapeutic effect by lanosterol [3][4][5], and our study may reflect both of these studies' results. Further studies are needed to elucidate the relationships between the effects of repair and structural collapse by lanosterol and to evaluate whether the application of lanosterol can return opaque lenses to transparency.…”
Section: Discussioncontrasting
confidence: 99%
“…This discrepancy may be caused by the differences in the models, since the structural changes in the lenses of the dogs and rabbits used by Zhao et al were mild in comparison with those of the SCR-C [3]. In contrast to the results of Zhao et al [3], Daszynski et al failed to find evidence that lanosterol has either anti-cataractogenic activity or binds aggregated lens proteins to dissolve cataracts [4]. Taken together, it was suggested that the difference in the severity and part (cortex and nucleus) of the lens opacification may explain the contradiction in the previous reports for therapeutic effect by lanosterol [3][4][5], and our study may reflect both of these studies' results.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…79 80 although recent studies have cast doubt on the efficacy of the identified oxysterols lanosterol and 25-hydroxy cholesterol to treat cataract. 81 The chemical chaperone 4-phenylbutyrate was used in mouse lenses to improve lens function in the genetic model of a cataract-causing connexin mutation (Cx50D47A) with limited success. 82 The search for small molecule inhibitors has been a consistent research goal over the decades with promising effects obtained with molecules such as pantethine, 83 rosmarinic acid and polyherbal preparations 84 and multifunctional antioxidants.…”
Section: Small Moleculesmentioning
confidence: 99%
“…The potential of such molecules to provide a nonsurgical treatment for cataract received a setback when detailed investigations failed to provide evidence that lanosterol or 25-hydroxycholesterol have anticataractogenic activity or bind aggregated lens proteins to clarify cataracts. 120 It is probably not possible to intervene in the spontaneous racemization, deamidation, or truncation events that characterize aged lens proteins since these appear to be driven primarily by heat and time. 16 On the other hand, it may be feasible to reduce protein-protein crosslinking since the dominant reaction involves nucleophilic addition of Lys or Cys residues.…”
Section: Can Arnc Be Prevented or Delayed?mentioning
confidence: 99%